Issues and challenges in managing enablers for the fire and Rescue Department Malaysia in search and rescue missions - Maidin, Siti Sarah; Othman, Marini; Arshad, Noor Habibah; Ahmad, Mohammad Nazir; Hamzah, Mohamad Nor; Salim, M. M. (WIT Press, 2015)
It is vital for organisations to manage enablers for value creation and delivery. Therefore, any matters that arise in managing enablers need to be addressed for the smooth running of an organisation operation. This research aims to highlight issues and challenges in managing enablers, in order to improve the Malaysian Fire and Rescue Department’s management and governance of enablers and the process and workflow of disaster operations. Observation, interviews and document reviews were carried out which resulted in an understanding of the process and procedures undertaken in a generic search and rescue operations, the required enablers, and an insight into the governance and management of these events. In order to present the result in a systematic manner, elements from the COBIT 5 framework are adopted to document the findings. The research concludes with recommendations on the use of the framework to improve the department’s operations in search and rescue missions.